2005
DOI: 10.1590/s0100-879x2005000800018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high hydrostatic pressure on the barrier properties of polyamide-6 films

Abstract: Little is known about the barrier properties of polymer films during high pressure processing of prepackaged foods. In order to learn more about this, we examined the influence of high hydrostatic pressure on the permeation of raspberry ketone (dissolved in ethanol/water) through polyamide-6 films at temperatures between 20 and 60ºC. Permeation was lowered by increasing pressure at all temperatures. At 23°C, the increasing pressure sequence 0.1, 50, 100, 150, and 200 MPa correlated with the decreasing permeati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Limited research works are carried out on packaging materials and heat sensitive nanoparticle under high pressure to assess its suitability for the food packaging and sterilization (Schmerder et al, 2005;Brigger et al, 2003). In that direction, studies on PLA under high pressure are very relevant and, in the same time food processors are looking for suitable packaging material that could be used for HPP.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research works are carried out on packaging materials and heat sensitive nanoparticle under high pressure to assess its suitability for the food packaging and sterilization (Schmerder et al, 2005;Brigger et al, 2003). In that direction, studies on PLA under high pressure are very relevant and, in the same time food processors are looking for suitable packaging material that could be used for HPP.…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect that must be considered to analyze the data listed in Table is that adsorption and diffusion in semi‐crystalline polymers depends on pressure and temperature. In general, the increase in temperature increases the free volume and, therefore, facilitates diffusion of small molecules within the polymer; in contrast, the increase in pressure decreases the free volume and, therefore, hinders diffusion . When the temperature of interest is below the glass transition temperature, the movement of the molecules is drastically restricted, and the free volume is small and does not change much with variations in pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer density increased with pressure, but there were no significant changes in density before and after HPP treatments, which implies that this effect recedes as the pressure is released unless irreversible structural changes occur in the polymeric material. Schmerder and others (27) reported that the 47% amorphous fraction of Nylon 6 measured by DSC was unchanged before and after pressure treatments up to 200 MPa at 20-60°C. Results of DSC experiments using LDPE films also showed that the crystallinity changes were not detectible after HPP at 200, 400, 600, and 800 MPa for 5 and 10 min at 25 and 75°C (23).…”
Section: Chemical Structure and Morphology Of Polymer Materials Durinmentioning
confidence: 95%
“…At 75 and 50°C, the PG migration was significantly higher than at 30°C. Schmerder et al (27) examined the influence of high hydrostatic pressure (60-400 MPa) on the permeation of an aromatic organic compound, raspberry ketone (4-(4-hydroxyphenylbutan-2-one)), in 10% ethanol through Nylon 6 films at temperatures of 20, 40, and 60°C. The permeated amounts of raspberry ketone during high pressure and after high pressure were measured by a 'bag-in-bag' method (37) and by an in situ permeation cell technique (36), respectively.…”
Section: Specific Migrationmentioning
confidence: 99%